How Euler did even more - Sandifer, Charles Edward, 1951- (MAA spectrum., 2015)
"The final 35 How Euler Did It columns are all collected in this book. ... They are lightly edited versions of the columns as they actually appeared on MAA Online between March 2007 and February 2010"--